2021
DOI: 10.21203/rs.3.rs-150255/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Caffeine and Pre-Workout Multi-Ingredient Performance Supplement on Reactive Agility and Countermovement Jump Height

Abstract: BackgroundThe purpose of this investigation was to examine the acute effects of a commercially available multi-ingredient performance supplement (MIPS) in comparison to caffeine, on reactive agility and jump height, in recreationally-trained handball male players. MethodsThe study followed a randomized double-blind, crossover design. Twenty-four individuals were treated with placebo, caffeine or multi-ingredient performance supplement (MIPS). Dosage of caffeine in caffeine supplement and MIPS contain the same … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Additionally, it has been shown that both caffeine and a multi-ingredient supplement positively influenced YRA performance. However, both supplements contained a moderate dose (5 mg/kg) of caffeine [ 30 ]. A higher dose of caffeine compared to the standard amount in the 4D dietary supplement may be necessary to elicit significant changes in YRA performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that both caffeine and a multi-ingredient supplement positively influenced YRA performance. However, both supplements contained a moderate dose (5 mg/kg) of caffeine [ 30 ]. A higher dose of caffeine compared to the standard amount in the 4D dietary supplement may be necessary to elicit significant changes in YRA performance.…”
Section: Discussionmentioning
confidence: 99%